A review on evolution of nitrogen-containing species during selective pyrolysis of waste wood-based panels. (1st October 2019) - Zhan, Hao; Zhuang, Xiuzheng; Song, Yanpei; Liu, Jianguo; Li, Sheng; Chang, Guozhang; Yin, Xiuli; Wu, Chuangzhi; Wang, Xinming
Graphical abstract: Highlights: Selective pyrolysis of WWPs on mechanisms & product properties are fully reviewed. N-containing pyrolytic gas is harmful but well treated by low temperature pyrolysis. N-enriched bio-oil shows good anti-bacterial/fungicidal & value-added properties. N-doped activated carbon serves as better wastewater adsorbent & electrode material. A new concept of fuel-N role switch (harmful to valuable) is proposed for utilization. Abstract: Waste wood-based panels (WWPs) are typical industrial biowastes with a huge annual production in the world, especially in China, which can be potentially utilized via selective pyrolysis. For a better understanding of clean and efficient resource utilization of WWPs, this study comprehensively provides a state-of-the-art overview of their selective pyrolysis in terms of pyrolysis mechanisms, formation characteristics and properties of pyrolysis products. It was noted that WWPs displayed a dual characteristic of excellent fuel quality and high fuel-N content due to co-existence of abundant lignocellulosic components and adhesives (referring to urea-formaldehyde resin, UFR). Pyrolysis of WWPs was intrinsically regarded as the interactions between lignocellulosic components and UFR under oxygen-free thermal conditions, leading to distinctive properties of pyrolysis products, especially referring to N-containing species. For pyrolytic gas, they were environmentally harmful but formed selectively to pyrolysis temperature. Subsequently, thermal pre-treatment at low temperatures was capable to favor their clean thermal utilization by reducing or regulating original fuel-N in WWPs. On the contrary, N-containing species in bio-oil and activated carbon were both economically valuable. Specifically, nitrogen compounds in bio-oil could manifest its excellent anti-bacterial/fungicidal and high value-added properties; nitrogen functionalities in activated carbon could guarantee its better adsorption capability and electrochemical performance. Hence, based on a new concept of role change of fuel-N from harmful to valuable species, by promoting its preferential conversion into solid/liquid phases, poly-generation of N-poor pyrolytic gas, N-enriched bio-oil and N-doped activated carbon from selective pyrolysis would be a promising technique for clean and efficient utilization of WWPs.